Penerapan Metode Single Exponential Smoothing Untuk Analisa Peramalan Penjualan - Agustinus Budi Santoso; Matheus Supriyanto Rumetna; Kristy Isnaningtyas (STMIK Budi Darma, 2021)
Pharmacies are part of the distribution category of drug sales and purchases. The demand for drugs becomes a focal point in the distribution of customers to drugs. Employees act to prepare and record drug purchase orders for the following month. The activity of sorting the available and unavailability of drug supply data often takes a long time. Exponential smoothing method is a method of forecasting moving averages by providing easy-to-analyze weighting. Time series sales data with Exponential Smoothing forecasting method is expected to be able to handle optimal inventory for controlling drug stock inventory. The use of data for the last 6 months as reference data for recording the past for forecasting experiments for the next 3 months. Experiments with different Alpha tests for accuracy in real life. The results of the experiment with alpha 0.3 are close to the real value in forecasting the next 3 months.